The future of disability law in India a critical analysis of the Persons with Disabilities (Equal Opportunities, Protection of Rights and Full Participation) Act 1995 - Kothari, Jayna (New Delhi ; Oxford : Oxford University Press, 2012)
According to the 2001 census, India has more than twenty million people suffering from various disabilities. However, disability law in India does not adequately address this issue. This book analyses the rights of the disabled people from the perspectives of equality and human rights.
Description based on print version record.
Includes bibliographical references and index.
Keywords: India; People with disabilities -- Legal status, laws, etc. -- India